Conflict of laws - O'Brien, John.; Smith, Raymond (London : Cavendish Publishing, 1999)
Cover title "Smith's conflict of law. First ed. by Raymond Smith.
Includes bibliographical references and index.
Keywords: European communities; Conflict of laws -- European Union countries